Utilization of dual stable isotopes to determine trophic structure in a mangrove - intertidal Mudflat of Johor Strait, Malaysia - Zulkifli, Syaizwan Zahmir; Hanapiah, Munirah; Md Joni, Amirul Azuan; Mukhtar, Aqilah; Mohamat Yusuff, Ferdaus; Ismail, Ahmad; Miyazaki, Nobuyuki (Enviro Media, 2016)
The coastal environment of the Johor Strait is gradually being altered, thus degrading the ecosystem's health. The present study was conducted to determine the food web in mangrove-mudflat ecosystem in vicinity to Sungai Pulai estuary as revealed by stable isotope analysis. A wide range of biota and sediments were collected and analyzed for δ 13 C and δ 15 N isotopic ratios. Results showed δ 13 C and δ 15 N values were ranged between-14‰ to-31‰ and 2.5‰ to 17.5‰, respectively. These data revealed that there are four trophic levels (primary producers up to tertiary consumers) that exist within the mangrove-mudflat ecosystem. Hence, a stable isotope analysis could be used to verify trophic structure in tropical mangrove ecosystem.